Emerging Insights Into the Role of Epigenetics and Gut Microbiome in the Pathogenesis of Graves’ Ophthalmopathy - Wang, Yan; Ma, Xiao-Min; Wang, Xin; Sun, Xin; Wang, Ling-Jun; Li, Xin-Qi; Liu, Xiao-Yan; Yu, Hong-Song (Frontiers in Endocrinology, 2022)
Graves' Ophthalmopathy (GO) is an organ-specific autoimmune disease which is often characterized by infiltration of orbital tissues and is considered as the most common extra-thyroid manifestation of Graves' disease (GD). Although genetic susceptibility has been found to be critical for the phenotype of GO, the associated risk alleles in a single gene are generally insufficient to cause the disease. Accruing evidence have shown that epigenetic disorders can act as the missing link between genetic risk and a clinically significant disease development. Abnormal epigenetic modifications can lead to pro-inflammatory cascades and activation of orbital fibroblasts (OFs) by promoting the various inflammatory response pathways and regulating the signaling molecules that is involved in the fibrogenesis and adipogenesis, thereby leading to the significant expansion of orbital tissues, fibrosis and inflammation infiltration. Additionally, emerging evidence have shown that the gut microbiome possibly drives the pathogenesis of GO by influencing the secretion of TRAb and Th17/Treg imbalance. This paper describes the latest epigenetic research evidence and progress made in comprehending the mechanisms of GO development, such as DNA methylation, histone modification, non-coding RNAs, and gut microbiome.